2018
DOI: 10.1038/s41533-018-0110-x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of association between critical errors in inhalation and health outcomes in asthma and COPD

Abstract: Inhaled medications are the cornerstone of treatment and management of asthma and COPD. However, inhaler device errors are common among patients and have been linked with reduced symptom control, an increased risk of exacerbations, and increased healthcare utilisation. These observations have prompted GINA (Global INitiative for Asthma) and GOLD (Global initiative for chronic Obstructive Lung Disease) to recommend regular assessment of inhaler technique in a bid to improve therapeutic outcomes. To better defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
89
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(94 citation statements)
references
References 34 publications
3
89
0
2
Order By: Relevance
“…Inhaler misuse and poor adherence were associated with an increased risk of hospitalization (p = 0.001), emergency room visits (p < 0.001), oral steroids (p < 0.001) and antimicrobial agents (p < 0.001) and poor disease control [2]. In contrast, patients who achieved a reduction in errors over time had improved outcomes [7]. In addition to the error rate when using inhalers, the patient's adherence to inhaler device therapy also plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Inhaler misuse and poor adherence were associated with an increased risk of hospitalization (p = 0.001), emergency room visits (p < 0.001), oral steroids (p < 0.001) and antimicrobial agents (p < 0.001) and poor disease control [2]. In contrast, patients who achieved a reduction in errors over time had improved outcomes [7]. In addition to the error rate when using inhalers, the patient's adherence to inhaler device therapy also plays an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Overall (children & adults, asthma & COPD) there is evidence that poor inhaler technique is associated with adverse outcomes. Kocks et al recently reported a systematic review of studies linking inhaler technique, assessment of errors, and disease outcomes (the majority studies being in asthmatics) (15). Although the 12 asthma studies had various outcomes most studies reported that inhalation errors were associated with worse disease outcomes.…”
Section: Key Question 3 Does It Matter If a Child's Inhaler Techniqumentioning
confidence: 99%
“…Inhaler handling errors and non-adherence can affect drug delivery and minimize treatment bene ts [5,6]. A large number of studies reported that inhaler errors came along with worse disease outcome in asthma or COPD patients [7]. Inhaler misuse was associated with an increased risk of hospitalization (p = 0.001), emergency room visits (p < 0.001), oral steroids (p < 0.001) and antimicrobial agents (p < 0.001) and poor disease control [2].…”
Section: Introductionmentioning
confidence: 99%
“…Inhaler misuse was associated with an increased risk of hospitalization (p = 0.001), emergency room visits (p < 0.001), oral steroids (p < 0.001) and antimicrobial agents (p < 0.001) and poor disease control [2]. In contrast, patients who achieved a reduction in errors over time had improved outcomes [7]. In addition to the error rate when using inhalers, the patient's adherence to inhaler device therapy also plays an important role.…”
Section: Introductionmentioning
confidence: 99%